2020
DOI: 10.5604/01.3001.0014.1787
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of shaping the railway track geometry in terms of their maintenance costs and capacity

Abstract: In Poland, due to the increase in investments made by railways in recent years, and thus the increase in the replacement value of transport infrastructure, the need for expenditure on infrastructure maintenance will increase in the next 30 years, or the development of the developed transport network will degrade. As part of the overall discipline of resource management, subdiscipline has emerged - infrastructure asset management. As part of the management of railway transport infrastructure, the demand for che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Machine learning is also used to detect railway defects such as corrugation [ 18 ] which the performance was satisfying. Besides the mentioned literature, machine learning and mathematical models were used in different areas such as supply chain [ 19 ], railway design [ 20 ], inspection scheduling [ 21 ], and cost management [ 22 ]. The summary of related studies is shown in Table 3 .…”
Section: Exploration Of Track Geometry Measurement and Predictionmentioning
confidence: 99%
“…Machine learning is also used to detect railway defects such as corrugation [ 18 ] which the performance was satisfying. Besides the mentioned literature, machine learning and mathematical models were used in different areas such as supply chain [ 19 ], railway design [ 20 ], inspection scheduling [ 21 ], and cost management [ 22 ]. The summary of related studies is shown in Table 3 .…”
Section: Exploration Of Track Geometry Measurement and Predictionmentioning
confidence: 99%
“…Based on the works carried out so far, it can be concluded that many of the risks arising during the entire project are a set of well-recognized risks, and a large part is unique to the works carried out within the railway infrastructure. Among the unique risks, there are risks related to the administrative process or obtaining consents, arrangements and administrative decisions [23], the impact of the implementation of engineering structures on the entire investment [24], risks related to the certification of railway infrastructure to the requirements of the Technical Interoperability Specifications [25], or also shaping track layouts based on time or cost criteria in the context of the entire investment life cycle [26].…”
Section: Risk Of Railway Construction Projectsmentioning
confidence: 99%
“…Болаттардың қызмет көрсету қасиеттеріне әсер ету дәрежесі бойынша оксидті металл емес қосындылар ерекше орын алады, олар көп жағдайда тотықсыздану реакцияларының өнімдері болып табылады [4]. Металл емес қосындылардың құрамы және соңғы оттегі мөлшері қолданылатын тотықсыздандырғыштармен, олардың құрамымен, санымен, реттілігімен және оларды балқымаға енгізу әдісімен анықталады.…”
Section: материалдар мен әдістерunclassified